Novel non-resonant, low-frequency pulse–current circuit for energy-efficient, low-noise transcranial magnetic stimulation - Tan, Xinhua; Tian, Zongrui; Tian, Jiasheng; Li, Yingwei; Shi, Jian (Frontiers in Neuroscience, 2025)
IntroductionTranscranial magnetic stimulation (TMS) is increasingly used for non-invasive neuronal activation. By harnessing a pulsed magnetic field, TMS induces electric currents that target the central nervous system. However, its efficacy is often limited by two critical challenges: excessive heat generation and the loud “clicking” noise produced by rapid coil pulsing. These limitations reduce both performance and patient comfort, hindering broader clinical adoption. To overcome these challenges, this study proposes a novel circuit architecture.Materials and methodsFirst, the principle of the triangular pulse–current waveform and its sensitivities were studied. The relationships between the waveform parameters and the induced electric field in the human brain were explored to ensure the necessary depolarization of the nerve membrane potential. Subsequently, theoretical analysis, calculations, and a particle swarm optimization algorithm were employed to optimize the pulse–current waveform. The aim was to substantially reduce both the clicking noise (vibration energy) and the ohmic heat generated by the TMS coil. As a result, three typical optimized triangular pulse–current waveforms were obtained under three distinct conditions. Finally, based on multi-module cascading and the principles of programmable TMS circuits, a non-resonant, low-frequency switching design and a voltage-dividing system were implemented. The voltage-dividing system—composed of a series resistor and inductor—together with multi-module cascading controlled by pulse-width modulation (PWM) sequences, was used to generate the desired pulse-voltage levels and durations on the TMS coil.ResultsThree variants of non-resonant, low-frequency TMS circuits were implemented based on the optimized pulse–current waveforms. Theoretical expressions for the optimal waveforms, including the IGBT-controlled voltage-dividing system, were presented. Each optimized triangular pulse–current waveform was modeled and simulated in MATLAB Simulink using these expressions. Moreover, by employing a low-frequency PWM controller, high-frequency switching is entirely avoided. The proposed circuit architecture, which combines a finite series of cascaded modules with the voltage-dividing network, can reproduce any of the optimized pulse–current waveforms as required.